2006
DOI: 10.1128/aem.02154-05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P Availability on Temporal Dynamics of Carbon Allocation and Glomus intraradices High-Affinity P Transporter Gene Induction in Arbuscular Mycorrhiza

Abstract: Arbuscular mycorrhizal (AM) fungi depend on a C supply from the plant host and simultaneously provide phosphorus to the colonized plant. We therefore evaluated the influence of external P on C allocation in monoxenic Daucus carota-Glomus intraradices cultures in an AM symbiosis. Fungal hyphae proliferated from a solid minimal medium containing colonized roots into a C-free liquid minimal medium with high or low P availability. Roots and hyphae were harvested periodically, and the flow of C from roots to fungus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 34 publications
5
25
0
Order By: Relevance
“…Nitrosospira or Nitrosospira-like AOB dominated in our soybean field, which is in agreement with previous observations (He et al 2007;Mendum et al 1999;Phillips et al 2000;Olsson et al 2006). However, an interesting observation was that chlorimuron-ethyl had chronic toxic effects on Nitrosospira cluster 3a and 3d groups but had few sideeffects on Nitrosospira cluster 3b and 3c.…”
Section: Fig 2 Nitrification Potential (Np) Error Bars Standard Devsupporting
confidence: 83%
“…Nitrosospira or Nitrosospira-like AOB dominated in our soybean field, which is in agreement with previous observations (He et al 2007;Mendum et al 1999;Phillips et al 2000;Olsson et al 2006). However, an interesting observation was that chlorimuron-ethyl had chronic toxic effects on Nitrosospira cluster 3a and 3d groups but had few sideeffects on Nitrosospira cluster 3b and 3c.…”
Section: Fig 2 Nitrification Potential (Np) Error Bars Standard Devsupporting
confidence: 83%
“…The AM fungi act as a carbon drain and the carbon consumption of AM fungi may exceed the nutritional or yield benefit produced . A recent study showed that carbon (C) flow to fungi actually increased during the initial period of infection under high P conditions (Olsson et al, 2006). In the present study, intermediate and high P supply tended to suppress the beneficial effects of the AM fungi.…”
Section: Dry Weightsupporting
confidence: 55%
“…However, the nutrients stored in spores may reflect not only the need for formation of new fungal biomass but also that of the plants that are being colonized. The establishment of new symbiotic relations could thus depend on the accumulation of plant-limiting nutrients in spores and their transport into the host roots for recognition of a nonparasitic intruder.The nutrient accumulation and distribution in AM fungal spores have not been studied in as much detail as carbon accumulation has (32), although there are clear links between the nutrient availability and C metabolism (16,17,18). Quantitative analysis of elemental composition in AM fungal mycelia is crucial for our understanding of the distribution of nutritional resources.…”
mentioning
confidence: 99%
“…The nutrient accumulation and distribution in AM fungal spores have not been studied in as much detail as carbon accumulation has (32), although there are clear links between the nutrient availability and C metabolism (16,17,18). Quantitative analysis of elemental composition in AM fungal mycelia is crucial for our understanding of the distribution of nutritional resources.…”
mentioning
confidence: 99%